Pengaruh Intensitas Penggunaan TikTok Terhadap Gaya Hidup Mahasiswa PGSD Universitas Muria Kudus - Zuhairina Firdaus; Shela Ayu Nadyarta; Moh Hadanil Atqo; Sekar Dwi Ardianti; Nur Fajrie (Universitas Palangka Raya, 2023)
Researchers see that the lifestyle of students who are more influenced by TikTok, which has now become a necessity for students, is no longer just entertainment or a communication tool, but more than that. So to find out how much negative and positive impact caused by Instagram social media, researchers are interested in doing this research. This study uses a descriptive quantitative approach. The instruments used in this method have been predetermined and well-organized so that they do not provide many opportunities for flexibility, imaginative input and reflexivity, namely the instrument in the form of a questionnaire (questionnaire). PGSD student at Muria Kudus University. This is supported by the results of the significance test (Sig) which shows that the Sig value is 0.013, which means it is smaller than the significance criterion (0.05). Therefore, it can be concluded that the regression equation model which is based on research data is significant. At the end of the study, all established success criteria had been met. In other words, this research is categorized as successful.